The politics of change? A critical analysis of power sharing in Kenya after Kofi Annan's mediation in 2008 - Hijnekamp, Elisabeth (Department of Political Studies, 2021)
This thesis explores the relationship between the mediation led by Kofi Annan in 2008 in Kenya, in the middle of the post-election violence that took place after the presidential elections, and the performance of the subsequent power sharing agreement. This study does so by focusing on five variables, as defined by Alexandre Raffoul, that are particularly relevant in understanding barriers to elite cooperation in power sharing settlements. By analysing problems relating to the balance of power, inside and outside spoilers, identity and political accountability problems and credible commitment problems, barriers to a successful power sharing agreement can be examined. To analyse how the mediation affected power sharing, five variables concerning the mediation are examined, namely the use of leverage, horizontal and vertical inclusivity, relationship-building and the content of the agreement. These five variables are combined one-on-one with the power sharing analysis to determine how mediation affects the performance of power sharing. This study argues that the type of mediation shapes the performance of power sharing, and that barriers to elite cooperation in the power sharing period can be addressed in the mediation phase of conflict to prevent future tensions. This knowledge can contribute to improving mediation efforts and make power sharing a more viable undertaking. By regarding mediation as an integral process to peacebuilding and to change mediation designs when applicable, conflict can be addressed in a more sustainable way that will bring long-term benefits.